(untitled) (University of Bucharest Review. Literary and Cultural Studies Series, 2025)
By using Freud’s theory of humour (1927) and his Jokes in their relation to the unconscious (1905), we follow the dominant features of the humour-pathos nexus from the late Victorian to the postmodernist literary decadence, taking in our stride the two peaking twentieth century modernist texts published by T.S. Eliot and James Joyce in 1922 Britain. We begin with Oscar Wilde’s popular The Importance of Being Earnest (1895) in relation to Walter Pater’s less well-known autobiographical novel Marius the Epicurean (1885), showing what relation the latter has with T.S. Eliot’s The Waste Land and James Joyce’s Ulysses. The modernist genial humour of Eliot’s 1939 Old Possum’s Book of Practical Cats is contrasted with Tom Stoppard’s in Rosencrantz and Guildenstern Are Dead (1966) and with the dark humour closer to pathos in The Life and Songs of the Crow (1970) by Ted Hughes.